Community's role in preventing child marriage: An analysis of models and community compliance with village policies - Mahmuddin, Mahmuddin; Mansari, Mansari; Melayu, Hasnul Arifin (Universitas Islam Negeri Ar-Raniry, 2023)
The presence of regulations that regulate the increase in the age of children fails to prevent child marriage. However, the existence of a community with an adequate child protection system has been able to prevent child marriage. This study aims to analyse the model developed by the community and the background to the emergence of community initiatives in efforts to prevent child marriage. The research method used in this study is a qualitative research method with a descriptive approach. Data was obtained by interviewing Reje Kampung, community facilitators, and NGO program officers. The research was conducted in Bener Meriah Regency. Data analysis was carried out qualitatively by selecting relevant data and then describing it systematically. The results showed that the model for preventing child marriage was carried out by forming a Cadre of Friends of Women and Children (SAPA), which is responsible for disseminating child protection issues. Second, establish a children's forum at the gampong level as a pioneer and reporter for child protection that continues to report on any incidents that affect children. Third, formulate regulations and policies in the village as guidelines for the community. The emergence of a child marriage prevention community was due to support from PKPM Aceh on the basis of support from UNICEF, which strengthened the issue of child protection from the roots (community) from 2022–2023. The community is strengthened by the issue of child protection and trains SAPA Cadres as the spearhead of fulfilling the rights of women and children in the village.